Intersecting SARS-CoV-2 spike mutations and global vaccine efficacy against COVID-19 - Tokhanbigli, Samaneh; Salami Ghaleh, Samira; Rahimian, Karim; Mahmanzar, Mohammadamin; Bayat, Saleha; Ahangarzadeh, Shahrzad; Moradi, Bahman; Mahmanzar, Reza; Wang, Yunliang; Oliver, Brian Gregory George; Deng, Youping (Frontiers in Immunology, 2025)
In line with encountering the world with the emergence of vaccine-resistance variants of SARS-CoV-2, 15,669,529 samples that received COVID-19 vaccines until April 2023 were investigated as two doses in the first phase and booster vaccinations in the second phase. The analysis shows that D614G and P681 mutations occurred in both phases. The E484 and Y655 mutations significantly emerged during the second phase. The 762-889 and 254-381 regions are revealed as conserved parts and could be considered in vaccine design. The Kruskal–Wallis test revealed a significant reduction in single mutations between populations with 20%–50% and those with 70%–100% vaccination coverage (p=0.017). The Mann–Whitney U test proposes a link between vaccination and suppression of viral mutation rates. Dynamic modeling suggests that key mutations have facilitated the virus’ evolution and immune escape. The study’s findings are crucial for understanding virus genome mutations, especially E614 and P681 in Delta and E484 and H655 in Omicron. This highlights the need to adjust strategies and strengthen global efforts in combating the pandemic.